Application of value stream mapping and simulation for the design of lean manufacturing systems: a case study. (22nd January 2010) - Anand, G.; Kodali, Rambabu
Many organisations both in India and abroad are implementing Lean Manufacturing (LM), but only a few companies have achieved a significant competitive advantage over other organisations. One of the reasons for this can be attributed to the lack of understanding by the managers regarding 'what changes will happen in an organisation, when it gets transformed by the principles and practices of LM ?' Even though LM tools such as Value Stream Mapping (VSM) can act as a blueprint for transformation, it suffers from various shortcomings. Hence, researchers suggested that simulation can be used in conjunction with VSM. However, a related literature review revealed that there are not many studies that deal with simulation and implementation of multiple LM elements in a time- and temperature-dependent batch manufacturing environment. Hence, in this paper, an attempt has been made to fill this gap, thereby providing a detailed application of modelling and simulation techniques beyond 'traditional' manufacturing.